m-Brand loyalty and post-adoption variations for the mobile data services: Gender differences. - Lee, Ya-Ching (Computers in Human Behavior, 2011)
This paper uses the value brand model in an attempt to determine the factors affecting post-adoption intentions through brand loyalty for the mobile data services. Data were collected online from 1266 respondents. The structural equation modeling was used to test the research model. The results show that post-adoption intentions are directly influenced by intangible attributes. Product deliverables and intangible attributes indirectly affect post-adoption intentions via m-brand loyalty. However, the results of current research do not show any effects of price on post-adoption intentions. The results also show genders differences in post-adoption intentions. Practical suggestions are provided. This paper advances our knowledge of post-adoption variations in business-consumer contexts and mobile business from the perspectives of utilitarian and non-utilitarian values of the mobile data services. This paper also contributes to the theory of post-adoption by offering across-gender examination.